Construction techniques and architectural design to reduce the level of radon inside buildings and therefore the risk of cancer - Burgos-Molina, Antonio Manuel; Ruiz-González, Óscar M.; González Vidal, Alejandro; Ruiz-Gómez, Miguel José (My University, 2022)
The incorporation of anti-radon membranes and forced ventilation and depressurization systems in buildings contributes to reduce the concentration of radon inside rooms. In this way, the exposure to radiation in its inhabitants is reduced, thus reducing the risk of cancer.
Keywords: Radón - Aspectos ambientales; Cáncer - Factores de riesgo; Ingeniería de estructuras - Aspectos sanitarios; Construction techniques and architectural design; Level of radon